Kinetics of Oxidation of Methionone by Chromic Acid in Sulphuric Acid in Sulphuric Acid Medium - Verma, Madhavi; Doss, Devyani (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of methionine by chromic acid in sulfuric acid medium has been investigated. The reaction is second order; first order each with respect to [methionine] and [chromic acid]. Iodometric titrations were done for study of rate of reaction. The rate constants (K2) have been computed by integration method as well as by graphical method.